Affinity Test of Generic and Patent Cream Preparations of the Corticosteroid Class with the Active Ingredient Mometasone Furoate - Soepriyadhy, Lusyana Mareta; Rosmiati, Meiti (Science Tech Group, 2025)
Increased pollution contributes to cases of atopic dermatitis, which is often treated with topical corticosteroid creams. This study assessed the preference for three creams from two generic industries and one patented product using an affinity test, namely the Hedonic Test and the Hedonic Quality Test. A total of 20 untrained panelists assessed aspects of odor, color, and texture using a 5-point hedonic scale. Data were analyzed using ANOVA and Duncan test. The results showed that texture had significant differences between Samples, with Sample B being rated the lowest. Aroma showed a tendency to differ, but not significantly, while colors were rated similar across all Samples. These findings indicate that product quality improvement should be focused on improving texture and aroma stability to increase consumer acceptance.